IEEE Military Communications Conference, 'Bridging the Gap. Interoperability, Survivability, Security'
DOI: 10.1109/milcom.1989.103896
|View full text |Cite
|
Sign up to set email alerts
|

Performance of fast frequency hopped noncoherent MFSK with a fixed hop rate under worst case jamming

Abstract: The use of error correction coding and diversity has been shown to be very effective against jamming in a fast frequency hopped M-ary !?SI< (FFH/AlFSI<) system. In the system design, it is usually implied that the hop rate is variable to accommodate the optimum design parameters. Unfortunately, systems such as satellite comniuncations may have the hop rate fixed before other system parameters are decided. This paper evaluates the pcrformance of FFHIAI FSK with a fixed hop rate for both uncoded and coded system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…We will refer to as the variance-scaled nominal corresponding to the nominal Of note is the fact that any specification of any one of the multiplicative constants fully determines the others through continuity whenever the divergence constraint is active according to Lemma 6. In turn, the single remaining degree of freedom is fully determined by the constraint (8). Hence, the optimization problem (7) has been reduced to the determination of an optimal value of and an optimal support decomposition Our goal is to reduce the choice of labeled intervals representing to one parameter, yielding a parametric expression for the worst case pdf with two degrees of freedom associated with the constraints (9) and (10). This desired reduction is the result of the following Lemma.…”
Section: Theorem 1: Given a Nominalmentioning
confidence: 99%
See 1 more Smart Citation
“…We will refer to as the variance-scaled nominal corresponding to the nominal Of note is the fact that any specification of any one of the multiplicative constants fully determines the others through continuity whenever the divergence constraint is active according to Lemma 6. In turn, the single remaining degree of freedom is fully determined by the constraint (8). Hence, the optimization problem (7) has been reduced to the determination of an optimal value of and an optimal support decomposition Our goal is to reduce the choice of labeled intervals representing to one parameter, yielding a parametric expression for the worst case pdf with two degrees of freedom associated with the constraints (9) and (10). This desired reduction is the result of the following Lemma.…”
Section: Theorem 1: Given a Nominalmentioning
confidence: 99%
“…Worst case power-constrained partial-band noise and multitone jamming for a variety of spread-spectrum transmission strategies are considered in [5]- [10]. Worst case amplitudeand power-constrained interference for an additive Gaussian channel with intersymbol interference is considered in [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several diversity-combining techniques have been proposed for mitigating the effects of PBNI on FFH system performance [16], [31], [32], [36]- [39], [41]- [45], [47], [48], [50], [61], [62]. The simplest diversity-combining receiver, namely the LCR, was proposed in [31] for an FFH/BFSK system in the presence of PBNI over non-fading channels.…”
Section: Pbni Mitigationmentioning
confidence: 99%
“…Both exact and approximate (multiple bound-parameter Cher-noff bound) solutions were obtained by making use of the statistical independence of the hopping symbols under two separate assumptions, i.e., with and without thermal noise. The authors concluded that for this type of receiver, when bit energy is fixed and the diversity level L is increased, the system performance is degraded because of the dominance of increased noncoherent combining loss for higher values of L. In [32], the throughput performance of an FFH/MFSK LCR was studied with a fixed hop rate over a non-faded environment. In [32], both the PBNI and MTI were considered in the analysis and it has been shown that for fixed data rate systems, the worst-case MTI is more effective against the FFH/MFSK LCR than the worst-case PBNI for M > 2 and the opposite is true for M = 2.…”
Section: Pbni Mitigationmentioning
confidence: 99%
See 1 more Smart Citation